1972
DOI: 10.1002/aic.690180619
|View full text |Cite
|
Sign up to set email alerts
|

The optimal control of a periodic adsorber: Part II. Theory

Abstract: and higher flow rates, for which adsorption rate limitations may become significant. Second, unless the permeability is constant, the optimal timing of the control sequence will vary and unless corrections for this are made in the control, suboptimal operation will result. To avoid this problem, adsorbent particles that resist abrasion and maintain a constant flow resistance should be used. The round particles used in this research were found to be satisfactory.Another factor that affects the operation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Other commercial applications are oxygen or nitrogen (but not both in the same process) production from air, octane improvement (using Union Carbide ISOSIV Process), and solvent recovery (Cassidy and Holmes, 1984;Keller, 1983). A variation of PSA, first described by Turnock and Kadlec (1971), and Kowler and Kadlec (1972), involves a one-column process driven by a square feed pressure variation applied to one end of the column, with slow withdrawal of a product stream from the opposite end. A process similar to this but using a different pressure cycle, i.e., a short feed and a long exhaust which result in better separation, has recently been commercialized for medical oxygen purposes (Jones and Keller, 1981).…”
Section: Conclusion and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Other commercial applications are oxygen or nitrogen (but not both in the same process) production from air, octane improvement (using Union Carbide ISOSIV Process), and solvent recovery (Cassidy and Holmes, 1984;Keller, 1983). A variation of PSA, first described by Turnock and Kadlec (1971), and Kowler and Kadlec (1972), involves a one-column process driven by a square feed pressure variation applied to one end of the column, with slow withdrawal of a product stream from the opposite end. A process similar to this but using a different pressure cycle, i.e., a short feed and a long exhaust which result in better separation, has recently been commercialized for medical oxygen purposes (Jones and Keller, 1981).…”
Section: Conclusion and Significancementioning
confidence: 99%
“…Most of them considered the adsorption of a single, dilute adsorbate (Pigford et al, 1969; Sweed and Wilhelm, 1969; Wankat, 1981; Hill et al 1981Hill et al ,1982Hill et al , 1983. Kadlec et al (1971Kadlec et al ( ,1972 modeled a single-column process similar to PSA for separating 28.4% N2 in CHI. In this work, bulk separation is studied both experimentally and theoretically for a mixture of 50/50 H2/CH4.…”
mentioning
confidence: 99%
“…Such scaling analyses have been carried out for adsorption (Wankat, 1987), chromatography (Wankat and Koo, 1988), isothermal PSA (Kowler and Kadlec, 1972;Suh and Wankat, 1990), and for adiabatic PSA processes (Rota and Wankat, 1990). This note extends these analyses to TSA processes.…”
mentioning
confidence: 88%
“…The goal is to keep pressure drop and separation constant while improving absorbent productivity. A dimensional analysis method (Kowler and Kadlec, 1972;Suh and Wankat, 1990;Rota and Wankat, 1990) will be presented.…”
mentioning
confidence: 99%
“…There is an increasing number of important industrial applications being found for temperature and pressure swing separation processes. Designs and performance models have been made and illustrated with various examples (Pigford et al, 1969(Pigford et al, ,1971; Kadlec et al, 1972Kadlec et al, ,1973Wankat et al, 1975Wankat et al, ,1978Hill et al, 1980Hill et al, ,1982. In these models it has been assumed that the adsorbed phase is in instantaneous equilibrium with the ~~ Correspondence concerning this paper should be addressed to R. T. Yang bulk flow phase of the fluid.…”
Section: Scopementioning
confidence: 99%